ASSESSMENT OF BIOCHEMICAL PARAMETERS OF CHRONIC KIDNEY DISEASE (CKD) PATIENTS IN DIFFERENT CITIES OF PAKISTAN. - Qamar Yasmeen1 , Summaira Yasmeen2 , Nauman Khursheed3, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT: BACKGROUND: A disorder known as chronic kidney disease affects the kidneys' normal filtration, reabsorption, secretion, and other functions. OBJECTIVE: This study was designed for assessment of biochemical parameters of chronic kidney disease (CKD) of non dialysis patients in different cities of Pakistan. METHODOLOGY: A total of 135 patients who were diagnosed with different stages of chronic kidney disease (CKD) and age above 40 years were enrolled in a cross-sectional observational questionnaire and laboratory base study. Their demographic and disease-related biochemical parameters were recorded and analyzed. Descriptive statistics was applied with frequency, percentage and Mean ± SD for all variables. RESULTS: All the CKD patients had elevated creatinine, uric acid and urea levels. The factors independently associated with CKD were older age, hypertension, diabetes, elevated systolic blood pressure, low hemoglobin levels, elevated ESR and history of coronary heart disease. The incidence of hypertension, diabetes, CHD and arthritis was 51.6%, 38.2, 21% and 28% respectively. Among electrolyte disorders, Hyperphosphatemia (5.5±2.2), hypocalcemia (7.5±1.8), and hyperkalemia (5.1±1.9) were found to be more prevalent in CKD patients. CONCLUSION: Biochemical and hematological parameters are deranged in patients with chronic kidney disease. Routine evaluation of these parameters is useful in the management of these patients.